Study of engineering properties of selected vegetable seeds - MISHRA, ALKA; SINHA, JAGNNATH PRASAD; KAUKAB, SHAGHAF; TOMAR, BHOOPAL SINGH (The Indian Journal of Agricultural Sciences, 2019)
Quality seed is the foundation block of vegetable production system. Proper post-harvest processing of seed is important to maximize yield, longevity, vigour, and overall quality. The engineering properties determination is the first and foremost step for the design of any seed processing, storage and handling machine or equipment. Engineering properties like geometric, gravimetric, frictional and aerodynamic properties of bottle gourd, sponge gourd, garden pea, and radish seeds have been determined at different levels of moisture content (7.5 % to 19 % dry basis). Results revealed a quadratic increase in all properties with moisture content except for gravimetric properties. The properties like sphericity (0.83), bulk density (710.61 kg/m3), true density (1109.79 kg/m3), angle of repose (26.41Â°), terminal velocity (10.13 m/s) and drag coefficient (0.92) were highest for garden pea seeds. Whereas, bottle gourd seeds exhibited maximum values for size (7.17 mm), projected area (115.68 mm2), porosity (53.4%) and coefficient of friction (0.727).